Investigation of Sediment Characteristics and Nutrient Content in Relation to Pilot Dredging at Kis-Balaton Water Protection System (Hungary) - Hilda Hernádi; András Makó; Zsófia Lovász; Sándor Szoboszlay; Péter Harkai; Judit Háhn; Mihály Kocsis; Eszter Schöphen; Zoltán Tóth; András Bidló; Márk Rékási; Árpád Ferincz; et al. (Hydrology)
The internal nutrient load of natural and artificial lakes is a worldwide problem. To minimize its potential risks, the dredging of the highly eutrophic shallow first reservoir of Kis-Balaton (Lake Hídvégi) is planned in the near future. Our study aimed to evaluate the potential effects of dredging and desiccation on water and sediment quality. Experimental dredging was carried out in the northernmost part of Lake Hídvégi (2023). The physical and chemical characteristics of the sediment and nutrient loss during desiccation were examined in a column experiment. The relationships between the properties of leachate and sediment were identified using principal component analysis (SPSS). Spatial variations in sediment particle size distribution, nutrient content, and other chemical parameters (e.g., organic matter) suggest that deeper core sampling than the depth of preliminary dredging is necessary for a more comprehensive assessment of potential impacts. We found that spatiotemporally varying the dominance of chemical and biological processes affects the amount of and changes in phosphorus fractions under lake-/sediment-specific conditions. The readily available calcium- and iron-bound phosphorus, texture, and organic matter content of the sediment play an important role in phosphorus fixation/release. Based on our results, dredging and desiccation are feasible within the intended operating parameters. The sediment’s composition does not preclude potential agricultural disposal.